Controls on Mg isotopic fractionation between deep mantle phases and relict signatures of a terrestrial magma ocean - Andrew M. Walker; Remco C. Hin; Tim Elliott (Geochimica et Cosmochimica Acta, 2026)

Magnesium isotope heterogeneity in oceanic island basalts - Xiao-Ning Liu; Remco C. Hin; Christopher D. Coath; Isaac Onyett; Bryony Rogers; Jamie Lewis; Tim Elliott (Earth and Planetary Science Letters, 2026)

Lunar mantle differentiation and Earth–Moon similarity constrained by Ni stable isotopes - Ke Zhu; Peng Ni; Qi Chen; Mahesh Anand; Meng-Hua Zhu; Tim Elliott (Earth and Planetary Science Letters, 2026)

Molybdenum isotope fractionation during low-temperature alteration of the upper ocean crust at DSDP sites 417 and 418 - Shuo Chen; Qiqi Xue; Yaoling Niu; Pu Sun; Pengyuan Guo; Joel B. Rodney; Tim Elliott (Geochimica et Cosmochimica Acta, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Deformation of the Ecuadorian Inter-Andean valley and surroundings from a combined InSAR-GNSS velocity field 2017–2023. - Pedro Alejandro Espín Bedón; John R. Elliott; Tim J. Wright; Susanna Ebmeier; Patricia Mothes; Milan Lazecky; Yasser Maghsoudi; Jack McGrath; Daniel Andrade (Journal of South American Earth Sciences, 2025)

Si isotope composition of Earth’s mantle and oceanic basalts - Xiao-Ning Liu; Martijn Klaver; Remco C. Hin; Christopher D. Coath; Michael Bizimis; Dmitri A. Ionov; Tim Elliott (Geochimica et Cosmochimica Acta, 2025)

Imaging viscosity after the 2021 Mw 7.4 Maduo earthquake: Insights on the regional rheology variation beneath the Bayan Har block - Zhen Li; Wei Xiong; Andrew Hooper; Zeyan Zhao; Yuan Gao; John R. Elliott; Tim J. Wright; Han Yue; Teng Wang (Earth and Planetary Science Letters, 2025)

Assessing the timing of deep ocean oxygenation from uranium elemental and isotopic compositions of ophiolites - Joel B. Rodney; Morten B. Andersen; Daniel Stubbs; C. Johan Lissenberg; Omar Gianola; Matthias Willbold; Tim Elliott (Earth and Planetary Science Letters, 2025)

Constraints from uranium and molybdenum isotope ratios on the origin of enriched mid-ocean ridge basalts - Joel B. Rodney; Morten B. Andersen; Bramley J. Murton; Tim Elliott (Earth and Planetary Science Letters, 2025)

Rethinking the science-policy interface for chemicals, waste, and pollution: Challenging core assumptions - Jen Iris Allan; Anwesha Borthakur; Fiona Kinniburgh; Moritz Petersmann; Angeliki Balayannis; Andrew Barry; Silke Beck; Kevin Elliott; Tim Forsyth; Anita Hardon; Hannah Hughes; Philip Macnaghten; et al. (Global Environmental Change, 2025)

Corrigendum to “Molybdenum isotope systematics of lavas from the East Pacific Rise: Constraints on the source of enriched mid-ocean ridge basalt” [EPSL 578, 2022/117283] - Shuo Chen; Pu Sun; Yaoling Niu; Pengyuan Guo; Tim Elliott; Remco C. Hin (Earth and Planetary Science Letters, 2025)

Detrital K-feldspar as a novel archive of continental crustal evolution using coupled in situ Rb Sr dating and Pb isotope analysis - Dan Bevan; Daniel Stubbs; Christopher D. Coath; Jamie Lewis; Tim Elliott (Chemical Geology, 2024)

Experimental constraints on barium isotope fractionation during adsorption–desorption reactions: Implications for weathering and erosion tracer applications - Alasdair C.G. Knight; Edward T. Tipper; Harold J. Bradbury; Alexandra V. Turchyn; Christoff Andermann; Heye Freymuth; Tim Elliott; Luke Bridgestock (Geochimica et Cosmochimica Acta, 2024)

Co-eruptive, endogenous edifice growth, uplift during 4 years of eruption at Sangay Volcano, Ecuador - Pedro Alejandro Espín Bedón; Susanna K. Ebmeier; John R. Elliott; Tim J. Wright; Patricia Mothes; Valérie Cayol; Yasser Maghsoudi; Milan Lazecký; Daniel Andrade (Journal of Volcanology and Geothermal Research, 2024)

Potassium isotope compositions of Mariana arc lavas and their sedimentary input - Joel B. Rodney; Théo Tacail; Jamie Lewis; Morten B. Andersen; Tim Elliott (Geochimica et Cosmochimica Acta, 2024)

Time scales and mechanisms of uranium uptake in altered ocean crust; observations from the ∼15 million year-old site 1256 in the eastern equatorial Pacific - Morten B. Andersen; Joel B. Rodney; Heye Freymuth; Flurin Vils; Michelle Harris; Kari Cooper; Damon A.H. Teagle; Tim Elliott (Geochimica et Cosmochimica Acta, 2024)

Deciphering interseismic strain accumulation and its termination on the central-eastern Altyn Tagh fault from high-resolution velocity fields - Dehua Wang; John R. Elliott; Gang Zheng; Tim J. Wright; Andrew R. Watson; Jack D. McGrath (Earth and Planetary Science Letters, 2024)

Mg and Fe isotope compositions of mid-ocean ridge basalts modified by Mg-Fe inter-diffusion during melt transport - Xiao-Ning Liu (刘效宁); Remco C. Hin; Christopher D. Coath; Tim Elliott (Earth and Planetary Science Letters, 2024)

Nickel isotope fractionation factors between silicate minerals and melt - Martijn Klaver; Tim Elliott; Dmitri A. Ionov; Michael Bizimis; Jasper Berndt; Stephan Klemme (Geochimica et Cosmochimica Acta, 2024)

Molybdenum isotope evidence for subduction-modified, recycled mafic oceanic crust in the mantle sources of ocean island basalts from La Palma and Hawaii - Matthias Willbold; Tim Elliott (Earth and Planetary Science Letters, 2023)

The magnesium isotopic composition of the mantle - Xiao-Ning Liu; Remco C. Hin; Christopher D. Coath; Michael Bizimis; Li Su; Dmitri A. Ionov; Eiichi Takazawa; Richard Brooker; Tim Elliott (Geochimica et Cosmochimica Acta, 2023)

Corrigendum to “The influence of crustal recycling on the molybdenum isotope composition of the Earth's mantle” [Earth Planet. Sci. Lett. 595 (2022) 117760] - Remco C. Hin; Kate E.J. Hibbert; Shuo Chen; Matthias Willbold; Morten B. Andersen; Ekaterina S. Kiseeva; Bernard J. Wood; Yaoling Niu; Kenneth W.W. Sims; Tim Elliott (Earth and Planetary Science Letters, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Future Ocean Observations to Connect Climate, Fisheries and Marine Ecosystems - Jörn O. Schmidt; Steven J. Bograd; Haritz Arrizabalaga; José L. Azevedo; Steven J. Barbeaux; John A. Barth; Tim Boyer; Stephanie Brodie; Juan José Cárdenas; Scott Cross; Jean-Noël Druon; Agneta Fransson; et al. (Frontiers in Marine Science, 2019)

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

The cost of reproduction: differential resource specialization in female and male California sea otters - Emma A. Elliott Smith; Seth D. Newsome; James A. Estes; M. Tim Tinker (Oecologia, 2015)

ERAP1 in the pathogenesis of ankylosing spondylitis - Emma Reeves; Tim Elliott; Edward James; Christopher J. Edwards (Immunologic Research, 2014)

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

Identification of novel Tapasin polymorphisms and linkage disequilibrium to MHC class I alleles - Anthony P. Williams; Steven Bevan; Mike Bunce; Richard Houlston; Kenneth I. Welsh; Tim Elliott (Immunogenetics, 2000)